Changes in society and language development - Igamnazarova, Nafisa (The Lingua Spectrum, 2025)
Economic, cultural, technological and political changes that occur in society affect language formation. This article reflects on the connection between social changes in society and language development, the Basic Laws of language development, the emergence of new words and phrases, vocabulary enrichment and grammar change. The article also outlines how language is changing as a result of modern technologies and globalization processes, the interaction of national and international cultures, the simultaneous development of language society, and the transformation of culture and identity into an important element.